Overview of Methods for Assessing Loss and Damage Associated with Climate Change - Trung Thang, Nguyen; Thi Ngoc Anh, Nguyen; Quy Trung, Tran; Canh Tung, Dao (VNU Journal of Science: Policy and Management Studies; Vol 38 No 2DO - 10.25073/2588-1116/vnupam.4378, 2022)
Loss and damage (L&D) caused by climate change (CC) has been defined as inevitable/unavoidable losses after the implementation of mitigation and adaptation measures. As climate change continue to be complicated and unpredictable, L&D will increase, especially for highly vulnerable countries like Vietnam. Therefore, the assessment of L&D caused by climate change is very important and necessary. This article presents the results of an overview of L&D assessment methods applied in the world. The review showed that, L&D assessment have either disaster risk reduction (DRR) or climate change adaptation (CCA) approach and is classified in qualitative and quantitative assessments or ex-ante and ex-post assessment. In general, the methods of assessing L&D caused by natural disasters have been developed and guided, whereas the methods of assessing L&D by climate change adaptation approach have not been popularly developed. Currently, the most popular method is still ex-post assessment while the models for evaluating/forecasting L&D in the future have not been widely applied in practice. The quantitative assessment of economic L&D is often applied for the ex-post assessment, while the qualitative assessment is often used for ex-ante assessment and applied to non-economic L&D.